Implementation of Digital Health Service Policies Based on Community-Based Research (CBR) to Improve Patient Accessibility in Remote Areas - Lindawati; Marniati (Help: Journal of Community Service, 2024)
Access to healthcare services remains a significant challenge for patients in remote areas, often due to geographical and infrastructural barriers. The integration of digital health services has emerged as a promising solution. This study explores the implementation of digital health service policies using the Community-Based Research (CBR) approach to improve patient accessibility in underserved regions. A CBR methodology was employed to engage stakeholders, including healthcare providers, local governments, and community members, in designing and evaluating digital health services. Data collection methods included participatory workshops, surveys, and interviews with key stakeholders to identify accessibility challenges and co-develop strategies. A pilot program involving telemedicine platforms and mobile health applications was implemented in three remote villages. Findings revealed that the collaborative approach significantly improved the adoption and usability of digital health technologies. Telemedicine services increased patient access to consultations by 45%, and the implementation of mobile health applications reduced travel times for medical care by 60%. Community involvement also led to increased trust and a better understanding of digital health solutions. The study demonstrates that leveraging the CBR approach facilitates the development of context-specific digital health solutions that address the unique needs of remote communities. However, challenges such as digital literacy and infrastructure limitations were identified, suggesting the need for further capacity-building initiatives. The CBR-based implementation of digital health service policies enhances patient accessibility in remote areas by fostering community engagement and tailoring solutions to local contexts.